2019
DOI: 10.1155/2019/6036979
|View full text |Cite
|
Sign up to set email alerts
|

Combined Diagnostic Efficacy of Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), and Mean Platelet Volume (MPV) as Biomarkers of Systemic Inflammation in the Diagnosis of Colorectal Cancer

Abstract: Background Systemic inflammation in colorectal cancer (CRC) may be reflected by neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV). This study was designed to investigate the efficiency of preoperative NLR, PLR, and MVP as a tool for the assessment of tumor characteristics in newly diagnosed patients with CRC. Patients and Methods For 300 patients and 300 healthy volunteers, complete blood counts with automated differential counts were performed. The NLR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
123
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 35 publications
8
123
0
3
Order By: Relevance
“…Furthermore, it was previously reported that patients with increased MPV had worse survival rates than those of patients with normal MPV levels . Additionally, one study found that the PDW levels of patients with CRC were higher than those in healthy participants but lower than those in adenomatous patients . That signified that PDW was an advantageous prognostic factor for the survival of patients with CRC.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, it was previously reported that patients with increased MPV had worse survival rates than those of patients with normal MPV levels . Additionally, one study found that the PDW levels of patients with CRC were higher than those in healthy participants but lower than those in adenomatous patients . That signified that PDW was an advantageous prognostic factor for the survival of patients with CRC.…”
Section: Discussionmentioning
confidence: 97%
“…Many scholars have reported that MPV levels might serve as potential biomarkers for the diagnosis and early recognition of different stages of CRC. 26,27 Furthermore, it was previously reported that patients with increased MPV had worse survival rates than those of patients with normal MPV levels. 28 Additionally, one study found that the PDW levels of patients with CRC were higher than those in healthy participants but lower than those in adenomatous patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N1 TANs has antitumor effect, while N2 TANs can promote the occurrence, development and metastasis of tumors [7]. In addition, A number of studies revealed that the increase of neutrophil count in peripheral blood was related to poor clinical outcomes in CRC, but the mechanism of this process was unclear [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%